An economic research on zakat compliance among muslim’s staff in UNIMAS - Shafinah Begum, Abdul Rahim; Hanani, Kaswadi (Kolej Universiti Islam Antarabangsa Selangor, Malaysia, 2014)
The increasing trend of unequal wealth distribution among Muslims in particular makes the issue of zakat compliance continue to be relevant. Existing works appear to focus on either the theoretical aspect of zakat as a religious obligation or how successful it can become when implemented accordingly. The purpose of this study was spurred by the information that the direct pay deduct of zakat on income at UNIMAS was suspected to remain low (30.5% based on TBS data) despite the service having been offered by the related authorities for more than a decade. Hence the objectives include the level of awareness and its root causes. Findings from the questionnaire survey showed that almost 86% of the respondents agree to know about the need to pay zakat on income (reflecting a high level of awareness). However, almost 50% of them admit to practice direct or an informal way of dispensing their responsibility which disables us from any documented evidences for further analysis. Thus we concluded that there were underlying reasons for their choice of payment of zakat on income and TBS can play a more active role to enhance their service quality. Among the factors respondents emphasized as influencing decision was religiosity and social belonging.